Answer:
x: C
y: A
z:
Explanation:
In a 45-45-90 triangle, the hypotenuse is larger than either of the legs by a factor of
. The length of x is therefore:
![12\cdot √(2)=12√(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/137ct9f3swyeskxbu0iz2hr9fqrnombq6i.png)
In a 30-60-90 triangle, the longer leg is larger than the shorter leg by a factor of
. Therefore:
![y=(12)/(√(3))=(12√(3))/(3)=4√(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/7bsfnn799ue4ir29cgck0e6g0d3jrmkm8b.png)
The hypotenuse of the 30-60-90 triangle is twice larger than the smallest leg, so it has a length of
.
By the pythagorean theorem, you can find z+y:
![z+y=\sqrt{(12√(2))^2-12^2}=√(288-144)=12\\\\4√(3)+z=12 \\\\z=12-4√(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/j1ystf66wzvwlpcl0w2dulo8o6d4r4g3c5.png)
Hope this helps!